Bibliometric Analysis of Hospital Smoking Policies: Research Trends, Influences, and Global Collaboration - Nurlia, Nurlia; Samsimbar, Samsimbar (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to analyze research trend developments, scientific impact, and global collaboration patterns in the field of hospital smoking ban policies using a bibliometric approach. Data were collected from the Scopus database using relevant keywords related to "hospital smoking policy" and analyzed with bibliometric software tools such as VOSviewer and Biblioshiny. The analysis results indicate a significant increase in the number of publications since 2000, with the United States, the United Kingdom, and Canada emerging as the main contributors. Dominant topics include smoke-free policies, health impacts on patients and staff, and the effectiveness of policy interventions. The visualization of collaboration networks reveals strong connections among developed countries, although collaborations involving developing countries remain limited. These findings provide a comprehensive overview of the research landscape concerning hospital smoking policies and highlight opportunities to strengthen cross-country cooperation to enhance the effectiveness of global health policies.